Periodontitis induced by orthodontic wire ligature drives oral microflora dysbiosis and aggravates alveolar bone loss in an improved murine model - Ai, Rongshuang; Li, Dingyi; Shi, Luyao; Zhang, Xiaonan; Ding, Zhiqiang; Zhu, Yiting; He, Yujuan (Frontiers in Microbiology, 2022)
Abstract Aim: To assess the contribution of polymicrobial disruption of host homeostasis to periodontitis progression in orthodontic wire ligation murine model. Methods: Orthodontic wire rings were inserted between the first and second molars of mice for 18 days for the orthodontic wire ligation mouse model, and Pg injection model and Pg-LPS injection model were used as controls. Alveolar bone loss and periodontal inflammation were analyzed by micro-CT, histological staining and qRT-PCR. Further, pyrosequencing of 16S rRNA gene amplicon was used to analyze the development of oral microorganism dysbiosis in the mice. Results: Micro-CT, TRAP staining and qRT-PCR showed that orthodontic wire ligation model led to more severe alveolar bone loss than Pg and Pg-LPS models. H&E staining and qRT-PCR demonstrated that stronger inflammatory response was induced by the orthodontic wire treatment compared to the other models. In addition, pyrosequencing of 16S rRNA gene amplicons revealed that the composition of oral microbiota presented a transition as the disease progressed and significant differences emerged in oral microbiota communities between orthodontic ligature mice and healthy controls. Furthermore, antibiotic treatment decreased both inflammation and alveolar bone loss in response to microbial community dysbiosis. However, no significant difference in bacterial community composition was observed in Pg and Pg-LPS models. Conclusions: Orthodontic wire ligation drove oral microbial community transitions that mimicked polymicrobial communities characterized by polymicrobial synergy and dysbiosis. Our improved model is suitable for further study of pathogenesis of periodontitis and exploration of corresponding treatment strategies.